Cardiac rehabilitation referral for PCI patients in Victoria, Australia - gender gap is closing but high-risk patients still miss out. (2nd July 2022) - Cartledge, S; Driscoll, A; Dinh, D; O'neil, A; Thomas, E; Brennan, A; Liew, D; Lefkovits, J; Stub, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Following percutaneous coronary intervention (PCI), outpatient cardiac rehabilitation (CR) is essential for secondary prevention.(1) However, uptake of CR is suboptimal(2), despite strong evidence demonstrating benefits. The aim of this study was to identify contemporary trends and predictors of CR referral of PCI patients in Victoria. Methods: A prospective, observational study using anonymised data from the Victorian Cardiac Outcomes Registry was undertaken. A total of 41, 739 patients were discharged following PCI over the study period (2017-2020) and included for analyses. Results: CR referral was 85%, with an increasing trend over time observed (p <0.001). Multivariable modelling identifying the independent predictors of CR referral included hospitals with high volumes of ST-elevation myocardial infarction patients (STEMI) (OR 4.89, 95% CI 4.41 – 5.20), STEMI diagnosis (OR 1.90, 95% CI 1.69 – 2.14), or treatment in a private hospital (OR 1.45, 95% CI 1.33 – 1.57). Predictors of non-referral included cardiogenic shock (OR 0.54, 95% CI 0.41 - 0.71), aged over 75 years (OR 0.62, 95% CI 0.57 – 0.68) and previous PCI (OR 0.66, 95% CI 0.62 – 0.70) (See Fig 1). PCI patients with an acute coronary syndrome who were referred to CR were also more likely to be prescribed four or more major preventive pharmacotherapies, compared to those who were not referred (90% vs 82%, p <0.001). Conclusion: Referral to CR in Australia for PCI patients has improved over time compared to previously published reports. Pleasingly, we did not observe a gender difference in rate of CR referral. However, older, more acute or co-morbid patients require consideration for CR referral as these patients may have the most to gain. We also included novel key hospital characteristics in our analysis, such as high-volume STEMI hospitals, which increase the odds of CR referral. Referral does not imply attendance, nor completion of CR and we need better linked data in Australia to examine these outcomes.